O ensino da açao de ler e suas contradiçoes - Arena, Dagoberto Buim [UNESP] (My University, 2010)
The article broaches the diffi culties found by the Brazilian school on teaching the act of reading to students in the beginning of their scholarship process. In order to analyze those diffi culties, one must start from the assumption that, historically, this teaching fi nds mostly basis on the emphasis on the fl uent pronounce without considering the reader’s intention to achieve meaning before the text, in social, historic and cultural situations. On this perspective, the school usually teaches students how to dominate some of the aspects of the linguistic system, for not comprehending that the act of reading is a cultural, plural, historical and social action, that uses this system. The article concludes that Latin America’s education has a path to run: the one to learn to teach the act of reading as a cultural practice, instead of simply understanding it as the domain of the linguistic system basis.

O artigo aborda as difi culdades encontradas pela escola brasileira para ensinar os alunos no início de seu processo de escolarização o ato de ler. Para analisar essas difi culdades, parte-se do pressuposto de que historicamente esse ensino apoia-se predominantemente na ênfase em pronúncia fl uente sem considerar a intenção do leitor de atribuir sentido diante do texto, em situações sociais, históricas e culturais. Nessa perspectiva, a escola costumeiramente ensina aos alunos como dominar alguns dos aspectos do sistema linguístico, por não compreender que o ato de ler é uma ação cultural, plural, histórica e social. O artigo conclui que a educação da América Latina tem um caminho a percorrer: o de aprender a ensinar o ato de ler como prática cultural, em vez de entendê-lo apenas como o domínio das bases do sistema linguístico.
Keywords: leitura